MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL MAKE A MATCH PADA MATA PELAJARAN IPS KELAS IV DI SDN 11 OKU - Yel mi Yunarti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
The problem of this study is the low student learning outcome and not yet applied learning model make a match in the subject of IPS. This research is a classroom action research.The technique of data collection is by observation and test. To analyze the data of student learning outcome used t test technique, t obtained is 2,776 while at t level 5 % =2,05, so t obtained >t table or mathematically 2,05 is than t table. That is, Ho rejected an ha accepted because t count>t table. Thus, the hypothesis put forward that therte is a siginificant increase in learning outcomes between after and before taught by using the model make a match acceptable the right. Keywords: outcome,make a match, IPS